Intellectual property rights, benefit-sharing and development of “improved traditional medicines”: A new approach - Willcox, M; Diallo, D; Sanogo, R; Giani, S; Graz, B; Falquet, J; Bodeker, G (Elsevier, 2015)
Ethnopharmacological relevance Protection of intellectual property rights and benefit-sharing are key issues for all ethnopharmacological research. The International Society of Ethnobiology has produced helpful guidelines on access and benefit-sharing which are widely viewed as a “gold standard” but the question remains how best to apply these guidelines in practice. Difficult questions include ownership of traditional knowledge, making appropriate agreements, and how appropriately to share benefits.